Association between Global Diet Quality Score (GDQS) and nutritional status among indonesian adolescents: A case study in Bogor District - Lorita Amanda Sardi; Lilik Kustiyah; Cesilia Meti Dwiriani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Adolescents are a population group highly vulnerable to nutritional problems due to rapid physical growth, increased nutrient needs, and the formation of long-term eating habits. Understanding the quality of their diet is essential for preventing both nutrient deficiencies and diet-related non-communicable diseases (NCDs). This study aimed to assess adolescent diet quality using the Global Diet Quality Score (GDQS) and its Indonesian modification (GDQS-I) and examine their association with nutritional status. The GDQS was developed to meet the need for a concise, sensitive, and globally applicable metric capable of evaluating both undernutrition and the risk of NCDs. This cross-sectional study was conducted from August to September 2025 and included 61 eighth-grade students from SMPN 2 Ciomas, Bogor. Dietary intake was assessed using repeated 2×24-hour food recalls, and nutritional status was determined through anthropometric measurements using the BMI-for-age index. The results showed that most adolescents had a normal nutritional status (82%); however, their diet quality was generally poor, with 67.2% categorized as high-risk based on the GDQS and 95.1% based on the GDQS-I. The Wilcoxon signed-rank test indicated significantly lower GDQS-I scores than GDQS scores (p<0.001). The Spearman correlation test found no significant association between diet quality and nutritional status (p>0.05). In conclusion, these findings suggest that the GDQS-I may be useful for screening dietary risks among Indonesian adolescents, although further validation is required.